The Tobelo Dalam People on Halmahera Island, Indonesia “Indigenous people or Vulnerable Group” - M Nasir Tamalene; Nam Rumkel; Adi F Mahmud (PALAR (Pakuan Law review), 2025)
AbstractThis study aims to examine the legal and social status of the "Tobelo Dalam" community on Halmahera Island, Indonesia, which has been ambiguously categorized as indigenous peoples or vulnerable groups. This research departs from the need to formulate the right policy approach in the context of protecting their basic rights as citizens. Using qualitative methods based on literature studies, field observations, and analysis of national and international regulations, this study found that the Tobelo Dalam community does not meet the criteria as an indigenous people according to United Nations standards and Indonesian positive laws. They are more appropriately classified as a vulnerable local ethnic group, given their limited access to education, health, economy, and legal protection. The results of the analysis show that this vulnerability status has an impact on the inhibition of the fulfillment of basic rights, thus demanding a more inclusive and adaptive approach to empowerment. The conclusion of this study emphasizes that government policies should be focused on strengthening the civil rights of the Tobelo Dalam community through a model of empowerment based on local needs and recognition as a vulnerable group, rather than mere recognition as an indigenous people. This study recommends the need for regulations that guarantee collective rights to land and natural resources for them as part of efforts to create just and sustainable social development. Keywords: Tobelo Dalam, indigenous peoples, vulnerable groups, citizens' rights, inclusive empowerment, Halmahera.